Comparison of the efficiency of ultrasound-guided ESPB and TAPB on postoperative analgesia: a system review and meta-analysis - Qian, Lu; Hu, Nian-qiang; Shen, Qi-hong; Ni, Kai (Frontiers in Medicine, 2025)
BackgroundThis meta-analysis systematically evaluates the analgesic efficacy of two regional anesthesia techniques - transversus abdominis plane block (TAPB) and erector spinae plane block (ESPB) in abdominal surgical procedures.MethodsThis PRISMA-compliant meta-analysis systematically queried PubMed, Embase, Web of science, and Cochrane library. Eligible studies were controlled clinical trials comparing ESPB and TAPB for postoperative analgesia, documenting pain scales, opioid use, and safety outcomes. Methodological rigor was evaluated per Cochrane criteria, with quantitative synthesis conducted via RevMan 5.4 using effect magnitudes (SMD/MD) and risk ratios (RR). Evidence certainty was graded using GRADE methodology.ResultPooled data from 21 RCTs (n = 1,293 patients) revealed better pain control during the 24-h postoperative period in the ESPB groups (2-h: MD = −0.68, 95% CI [−1.04, −0.32], p < 0.05). Also, postoperative opioid consumption was significantly reduced in the ESPB group (MD = −1.25; 95% CI [−1.66 to −0.85]; p < 0.05). No significant differences were observed in complication occurrence (RR = 1.13, 95% CI [0.75, 1.71], p > 0.05).ConclusionCurrent evidence indicates that ESPB demonstrates superior postoperative analgesic efficacy and reduced opioid requirements compared to TAPB, while maintaining comparable safety profiles.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42021275992.